PERANCANGAN SISTEM INFORMASI PEMESANAN OLI BERBASIS DEKSTOP PADA PT. GARDAMAS SURYA LESTARI CIBINONG - Kuswandi, Kuswandi; Syah, Donny Oktavian; Akhmal, Akhwanul; Hariyanto, Hariyanto (POLITEKNIK LP3I JAKARTA, 2020)
This research is motivated by the results of the author's observations and experiences at PT. Gardamas Surya Lestari, that the oil sales process is still done manually and is very dependent on physical data. Information system design at PT. Gardamas Surya Lestari aims to identify the needs of companies in the operational management of their business processes related to order data, current inventory. This aims to create an integrated system that can answer all the needs of the company in carrying out its business operations and facing competition from competitors. The methods used in writing this paper are surveys, literature reviews, and analysis of current business processes in the company. The results of the analysis of all the company's needs will be documented using the unified modeling language method. With this information system, all business operations within the company are facilitated with more perfect automation compared to the previous system, in addition to minimizing data loss or errors that often occur as a result of storing transaction data in physical form and not being organized.Keywords : Ordering, Design, Information System.